(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Chronic constipation is a prevalent gastrointestinal disorder associated with infrequent or difficult bowel movements and reduced quality of life. Pharmacological options often provide limited long-term relief and carry adverse effects. This study evaluated an integrative approach combining naturopathic dietary modifications and yoga-based practices. Materials and Methods: Thirty adults with clinically diagnosed chronic constipation underwent a 90-day intervention comprising fibre-rich dietary counselling and structured yoga practices aimed at improving gastrointestinal motility and abdominal function. Outcomes were assessed using the Patient Assessment of Constipation Symptoms (PAC-SYM), Constipation-Related Quality of Life Questionnaire (CRQOL), and Modified Bristol Stool Scale (MBSS). Statistical analyses included paired t-tests and repeated measures ANOVA. Results: Marked improvements were observed across all domains. PAC-SYM scores declined by 42.5% (10.62±1.80 to 6.10±1.17; p<0.0001, d=4.467), indicating reduced symptom severity. CRQOL scores improved by 45.2% (99.03±7.45 to 54.31±5.58; p<0.0001, d=11.963), reflecting better physical comfort and psychosocial well-being. MBSS outcomes demonstrated a 46.6% reduction in constipation burden (14.99±0.61 to 8.00± 0.50; p<0.0001, d=15.873), with stool consistency approaching normal. Large effect sizes (η²=0.68–0.88) confirmed robust treatment effects. No adverse events or dropouts occurred. Conclusion: An integrative regimen of yoga and naturopathic dietary modification significantly alleviated symptoms, normalized stool patterns, and enhanced quality of life in chronic constipation. This safe, non-pharmacological approach may serve as an effective alternative or complement to conventional therapy, warranting validation through larger randomized controlled trials.